A newly developed wrapping method for scintillator detectors. Issue 1 (January 2016) - Stuhl, L; Krasznahorkay, A; Csatlós, M; Algora, A; Gulyás, J; Kalinka, G; Kertész, Zs I; Timár, J
Abstract: A neutron spectrometer, the European Low-Energy Neutron Spectrometer (ELENS), has been constructed to study exotic nuclei in inverse kinematics experiments. The spectrometer consisting of scintillator bars can be used in the neutron energy range of 100 keV to 10 MeV. To increase the light collection efficiency a special wrapping method was developed for each bars of ELENS. By using the specially heat treated reflector foil 15-20% better light collection is available. The development of wrapping process, the results of the test experiments are also presented.